Obstructive Sleep Apnea Detection Using Lomb-Scargle Periodogram Method - Kavuran, Gurkan; Yeroglu, Celaleddin (Ieee, 2018)
In this study, the power spectral density of the heart rate signal was investigated by the Lomb-Scargle Periodogram method for obstructive sleep apnea (OSA) estimation. Sleep apnea, which occurs as a result of respiratory failure during sleep, is interpreted by scoring polysomnographic signals. One of these signals, Electrocardiogram (ECG), contains noise in its structure and exhibits irregular alteration. In this study, the power spectrum of the heart rate variability (HRV) was obtained based on filtered ECG signals. Analyzes in the presence of OSA and in the absence of OSA have shown that deviations occur in the high and low frequency components of the HRV.
Obstrüktif Uyku Apnesinin Lomb-Scargle Periodogram Yöntemi ile Teşhisi
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Obstructive Sleep Apnea; Lomb-Scargle periodogram; Electrocardiogram; Heart rate variability